INNOVATIVE APPROACH TO THE PROCESS OF PEDAGOGICAL MODELING OF STUDENTS - A. A. Umirov (American Journals, 2024)
The origin and development of innovations in education, their influence on the development of innovative mechanisms in the educational process, as well as an innovative approach to the process of pedagogical modeling of students are considered. The main attention is paid to approaches to the theory of modeling the educational process and types of models of educational institutions.
Keywords: Innovations, pedagogical innovations, innovative approaches, innovative modelling.